Breast feeding during Covid-19 pandemic: knowledge and intention study - Mazlan, Nurul Atikah Natasha; Muhd Helmi, Muhd Alwi; Abd Rahman, Mohd Aizuddin; Hasan, Taufiq Hidayat (International Islamic University Malaysia, 2022)
Introduction: COVID-19 pandemic affects breastfeeding practice in various ways. Various factors could affect the level of knowledge on the risk and benefit of breastfeeding during a pandemic and the intention of women to breastfeed. This study aims to measure the knowledge and the intention to breastfeed during COVID-19 pandemic and the associated factors. Materials and methods: A cross-sectional study was conducted using online selfadministered, validated questionnaire on 291 Malaysian women. Respondents were International Islamic University Malaysia Kuantan staff and visitors who gave birth between June 2021 and June 2022, identified through a convenient sampling method. The questionnaire consisted of 19 items that assessed knowledge on risk and benefit of breastfeeding during pandemic and 17 intention to breastfeed during pandemic items with three likert-scale response options. Prevalence of respondents with adequate knowledge and high intention to breastfeed were calculated. Mean scores between respondents with different sociodemographic backgrounds were compared using one-way ANOVA or t test. Results: Eighty percent of respondents have adequate knowledge (score more than 50%) and 73% of them have a high intention (score more than 50%). There was a fair correlation between knowledge and intention to breastfeed (r 0.439, p 0.001). Education level, previous breastfeeding experiences, and gestational age of the infant’s were significantly associated with the intention to breastfeed during COVID-19 pandemic. Conclusion: Providing knowledge alone may not be sufficient to promote breastfeeding owing to the only fair correlation between knowledge and intention.